Short- and Long-term Effects of Support Visibility on Support Providers' Negative Affect. (7th September 2019) - Marini, Christina M; Wilson, Stephanie J; Tate, Ashley M; Martire, Lynn M; Franks, Melissa M
Abstract: Objectives: Seminal research with spouses of chronic pain patients indicates that providing patients with instrumental support can be either costly or beneficial for spouses' well-being. Drawing from the invisible support literature, this study evaluated the extent to which patients' recognition of spouses' support moderated daily and long-term associations between spouses' support provision and negative affect. Method: Data came from a sample of spouses ( N = 145) of knee osteoarthritis (OA) patients, and the patients themselves. Participants completed a baseline interview, 22 days of daily diaries, and two follow-up interviews 6 and 18 months after baseline. Multilevel models were estimated to test study hypotheses. Results: As expected, support visibility moderated daily and long-term associations between spouses' instrumental support provision and negative affect. Spouses reported elevated levels of negative affect in response to providing patients with extra care and attention, but only when their support was not recognized (i.e., reported) by patients. Discussion: Findings from the current study pinpoint support visibility as a protective factor that may mitigate negative short- and long-term effects of spousal instrumental support provision on spouses' negative affect. Promoting patients' awareness of their spouses' support may offset negative emotional consequences of caregiving in the context of chronic health stressors.